Neurotransmitter receptors - Hucho, Ferdinand, 1939- (New comprehensive biochemistry, 1993)
This comprehensive compilation provides a wealth of information on receptor sequences produced by recombinant DNA techniques used in combination with classical biochemistry. To minimize redundancies in this wealth of information, only a few receptors (some of which are typical for a whole group of similar receptors, others which are presently of special interest) are dealt with in a full-size chapter. Others are represented in the TIPS Receptor Nomenclature Supplement which is included as a special feature in this book, making this volume more useful as a receptor handbook.